Digital Transformation in Business Management: Facing the Era of a Connected Society - Iskandar, Agung Nugraha; Azhmy, Muhammad Fauzan (ProBisnis : Jurnal Manajemen, 2024)
The objective of this article is to investigate the role of digital transformation in the context of business management, in facing an increasingly connected society through technology. The article aims to provide insights into how companies can leverage digital transformation to enhance competitiveness, operational efficiency, and create superior customer experiences. The research methods utilized by the author include literature review and analysis of relevant case studies. The literature review covers the latest developments in digital transformation in business management, including technological advancements, trends, and challenges faced. Case studies are analyzed to understand how companies from various industries have successfully implemented digital transformation in their management strategies. The results of this article depict that digital transformation plays a crucial role in shaping and reshaping the current business landscape. By adopting digital technologies such as data analytics, artificial intelligence, and digital marketing, companies can improve data-driven decision-making, enhance operational efficiency, and create more personalized and relevant customer services.